Effects of Corticosteroids on Human Monocyte Function - Rinehart, John J. (1974)
This report examined the effect of corticosteroids in vitro on human peripheral blood monocytes, essential cells in both immune and nonimmune cellular defense mechanisms. Monocyte chemotaxis in response to sera, Escherichia coli filtrate, and lymphokine chemotactic factor was markedly reduced (P < 0.01) by hydrocortisone succinate (HCS) at 16 μg/ml. Methylprednisolone succinate and unesterified hydrocortisone produced similar impairment of monocyte chemotaxis while two drugs which unmodified do not enter cells, hydrocortisone phosphate (HCP) and cortisone acetate, had no effect on chemotaxis. HCS also significantly impaired monocyte random migration at 16 μg/ml. Monocyte bactericidal activity was reduced by HCS at 16 μg/ml (P < 0.01)) but was not affected by HCP even at 120 μg/ml. In comparison, HCS did not alter granulocyte chemotaxis even at 500 μg/ml, and bactericidal activity was reduced at 16 μg/ml (P < 0.01). Monocyte phagocytosis of cryptococci was reduced only 20% (P < 0.05) at 120 μg/ml. HCS at 120 μg/ml did not alter monocyte base-line or postphagocytic hexosemonophosphate shunt activity, viability by trypan blue exclusion, adherence to tissue culture flasks, or surface binding of IgG globulin. These corticosteroid-induced defects in monocyte function may contribute to reduced cellular defense during corticosteroid therapy.